2014
DOI: 10.2166/wst.2014.396
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting performance of support vector machine for the Poyang Lake's water level

Abstract: The growth of forecasting models has resulted in the development of an excellent model known as the support vector machine (SVM). SVMs can find a global optimal solution equipped with kernel functions. This research trains and tests the SVM network and constructs the support vector regression prediction model by using hydrologic data. Six hydrologic time series were calculated by different kernel functions (namely, linear, polynomial, radial basis function (RBF)), to determine which kernel is the more suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…During the dry season, the water level drops, and the beach is exposed; it then rises during the wet season and the landscape is very different from that in the dry season (Yuan et al, 2015). The water level in the lake is generally highest between June and August, and lowest between December to February (Lan, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…During the dry season, the water level drops, and the beach is exposed; it then rises during the wet season and the landscape is very different from that in the dry season (Yuan et al, 2015). The water level in the lake is generally highest between June and August, and lowest between December to February (Lan, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…For example, variance partitioning showed that only a small part of variability in water level was attributable to stochastic changes, which is fully comprehensible since it is a strongly autocorrelated variable (Lan, 2014). However, the correlations of phytoplankton with stochastic component of water level remained significant, which is not easy to interpret.…”
Section: Critical Assessment Of the Statistical Methodsmentioning
confidence: 98%
“…Herein, the training set is for fitting the model with its labels (training phase) that define the meaning of the supervised approach, the validation set is for adjusting or tuning the parameter constraints of the trained algorithms, and the testing set is for measuring or evaluating the performance of the algorithms previously trained and validated. 61 27 and Lan in 2014 32 have splitted their database inputs for evaluating the performance of the models used. As listed in Table 1, the splitting ratio employed is in the range of 0.05-0.50.…”
Section: Splitting Of Inputs For Evaluating the Algorithmsmentioning
confidence: 99%